Cultural revitalization for tourism development from an Indigenous perspective: the case of Ta Oi people, A Luoi District, Thua Thien Hue province, Vietnam - Nguyen, Thu-Suong Thi; Phan, Diem-Huong Thi; Doan, Diem-Hang Le; Chau, Minh-Ngoc Thi; Doan, Thanh-Thuy Thi (Jessica) (Frontiers in Sustainable Tourism, 2025)
IntroductionPreserving and revitalizing culture to ensure authenticity for tourism development is a critical concern, especially as modern societal changes have eroded numerous traditional cultural values. Most local tourism development efforts primarily focus on meeting tourists' demands, often overlooking the perspectives of local communities who practice these unique cultures. This study, grounded in constructivist grounded theory, emphasizes the importance of conducting research from the local perspective to maintain authenticity in cultural preservation and to balance the interests of local people, tourists, and stakeholders.MethodsThe qualitative research method employed included fieldwork and focus group discussions conducted in A Luoi district, Thua Thien Hue province, Vietnam. Fieldwork and participation observations allow to capture information about the research area as well as the experiences and behaviors of the local community. Furthermore, focus groups were conducted with 20 Ta Oi people, divided into two groups: the elderly (aged over 50) and the young people, to gather thorough and various information from their perspective on the meaning and the revitalization of local culture. The data were analyzed thematically.ResultsThe findings reveal that the Ta Oi people have revitalized four key cultural practices through tourism, including Dzeng weaving, traditional landscapes and architecture, traditional cuisine, and traditional art performances, rituals, and beliefs. In addition, cultural revitalization is also mentioned through people's perception of the authority's role and the adjustment of cultural activities toward tourism development. These practices have been adapted to fit the modern context, demonstrating that cultural revitalization is not about restoring traditions in a static form but rather reconstructing them to meet evolving societal and economic demands.DiscussionThe research illustrates the adaptability and creativity of local people in preserving and revitalizing traditional culture, along with their enthusiasm and willingness to take action. Cultural preservation is not a top-down process; instead, it is co-created by the Indigenous community itself, shaped by differing viewpoints between elder and younger generations. This ensures that while cultural traditions may evolve, they are still rooted in the values and identity of the Indigenous people, rendering the cultural revival process both sustainable and meaningful in the context of tourism. The research findings serve as a crucial foundation for guiding local government policies on cultural preservation and tourism development.